Chebyshev type inequality containing a fractional integral operator with a multi-index Mittag-Leffler function as a kernel - Jangid, Kamlesh; Purohit, Sunil Dutt; Nisar, Kottakkaran Sooppy; Araci, Serkan; Aracı, Serkan (De Gruyter Open Ltd)
In this paper, we derive certain Chebyshev type integral inequalities connected with a fractional integral operator in terms of the generalized Mittag-Leffler multi-index function as a kernel. Our key findings are general in nature and, as a special case, can give rise to integral inequalities of the Chebyshev form involving fractional integral operators present in the literature. © 2021 Walter de Gruyter GmbH, Berlin/Boston 2021.
Keywords: Chebyshev integral inequality; fractional integral operators; Mittag-Leffler function; multi-index Mittag-Leffler functions